Representasi Etnis, Agama, dan Gender dalam Buku Teks Utama Bahasa Inggris Sekolah Dasar - Sukraini, Niwayan (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The Merdeka Curriculum emphasizes contextual teaching and learning (CTL) that is meaningful and applicable, yet its implementation can be hindered without Culturally Responsive Pedagogy (CRP). Textbooks, as primary learning media, play a strategic role in representing ethnic, religious, and gender diversity. Preliminary observation of Indonesian English textbooks indicated unequal representation, leading this study to address three research questions: (1) how ethnicity, religion, and gender are represented in the textbook, (2) to what extent these representations reinforce or challenge existing stereotypes, and (3) what implications they have for shaping students’ perceptions of diversity and equality. This study employed qualitative content analysis with a descriptive approach on My Next Words Grade 6 – Student’s Book for Elementary School (2022), focusing on Unit 8 “I Will Go to Dufan.” Findings reveal a gender imbalance, with male characters more dominant (61%) than female characters (39%), reflecting traditional stereotypes but also showing some inclusive portrayals. Hijab-wearing girls are actively represented, challenging passive stereotypes, while ethnic representation remains minimal, limited to cultural symbols. The study concludes that the textbook retains gender and ethnic bias despite progressive steps in religious and cultural aspects. Recommendations include enhancing female and minority ethnic representation, strengthening teachers’ critical literacy, and enforcing stricter curriculum policies on equity.